2001
DOI: 10.1080/02699050010022662
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of chronic aggressive behaviour 10 years after brain injury

Abstract: This study demonstrates the successful management of aggressive behaviour with a client 10 years post-injury in a small, residential neurorehabilitation unit. The case presented is unusual for two main reasons. First, it proved possible to significantly modify previously chronic challenging behaviour many years after brain injury had been sustained. Secondly, the rehabilitation environment in which treatment was conducted did not comprise a highly specialized neurobehavioural service, Instead, staff were speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 25 publications
0
28
0
4
Order By: Relevance
“…Wood, McCrea, Wood, and Merriman (1999) found that neurobehavioural rehabilitation still produced positive changes in patients more than 5 years post-injury although the changes were not as great as for those receiving rehabilitation sooner after injury. Watson, Rutterford, Shortland, Williamson, and Alderman (2001) describe a single case which suggests that positive changes in behaviour can be achieved more than 10 years post-injury, given a lengthy period of input. Furthermore this was established with a minimum of professional staff.…”
Section: Introductionmentioning
confidence: 96%
“…Wood, McCrea, Wood, and Merriman (1999) found that neurobehavioural rehabilitation still produced positive changes in patients more than 5 years post-injury although the changes were not as great as for those receiving rehabilitation sooner after injury. Watson, Rutterford, Shortland, Williamson, and Alderman (2001) describe a single case which suggests that positive changes in behaviour can be achieved more than 10 years post-injury, given a lengthy period of input. Furthermore this was established with a minimum of professional staff.…”
Section: Introductionmentioning
confidence: 96%
“…8 Third, it supplies periodic, maintenance rehabilitation for individuals with chronic, progressive neurological disorders, but who again, do not require hospitalization. 9 This growing field is grounded in a belief in the importance of on-going rehabilitation for neurological illness; i.e., that neurorehabilitation can be beneficial even years after an injury or illness event 10 and that long-term and recurrent rehabilitation may help individuals maintain or advance their functional status. 11,12 It is further argued that such community maintenance rehabilitation does not require the intensive and expensive care of an acute, inpatient hospital, but rather, specialized rehabilitation can be provided on an outpatient basis.…”
Section: Introductionmentioning
confidence: 99%
“…social behaviours) are emerging [5]. In general, TBI has been associated with cognitive [6], academic [7] and behavioural impairments [8]. Of these sequelae, behavioural impairments have been reported to be most persistent over time and of great concern.…”
Section: Introductionmentioning
confidence: 99%